ASSESSMENT OF MARKET VOLATILITY DYNAMICS IN THE PERIODS OF SYSTEMIC INSTABILITIES - I. E. Denezhkina (Real Economics Publishing House, 2014)
The new method of estimation of the values of the VaR using the modified GARCH model is presented, effectively assessing risks as in the quiet periods of financial market and at the same time the system instabilities.To check the efficiency of the estimation of the VaR used for statistics, calculated as on total time interval, and in the sliding window. Results of local and global use of these statistics are in good agreement with each other, with the statistics computed in sliding window provide information about the uniformity of the effectiveness of calculating VaR. In particular, the effectiveness of the assessment of VaR practically did not change during the periods of the significant rise in prices in comparison with the «quiet» periods.